Bioactive coatings on double depth laser-textured zirconia substrates: mineralization behaviour and cell adhesion - Pereira, Luís Eduardo Martins (2023)
Teeth are exposed to daily factors that lead to their deterioration. Thus, dental implants improve people’s daily lives each year. The industry has been increasingly seeking new materials and techniques to improve dental implants efficiency, enhancing their mechanical properties and osseointegration. Zirconia, due to its good mechanical properties and outstanding aesthetic and antibacterial properties, has recently emerged as an alternative to titanium, a well-documented material in dental implants that has been available in the industry for several years. Lately, research studies have been exploring new surface functionalization methods to enhance zirconia dental implants performance. It is known that inducing surface roughness improves implant osseointegration, so the industry uses methods such as grit blasting and acid etching to produce random textures in zirconia surfaces. More recently, it has been proposed that designed textures, achieved via laser texturing, create an improved environment for cell attachment, differentiation, and proliferation. In this study, samples of 3 mol% yttria-stabilized zirconia (TZ-3YSBE) were submitted to different laser-induced textures: Thin - periodic spots with low depth; Coarse - Cross-linked deep grooves; Mixed - combination of the previous two. The objective was to explore the effect of different textures on cellular activity and the propensity of the double-depth texture (Mixed) to induce an improved osseointegration. Moreover, laser technology was also explored as a bioactive coating treatment. The samples were coated with S53P4 bioactive glass and submitted to laser or conventional treatment. The laser treatment induced an amorphous coating, while the conventional treatment created a partially crystalline coating. The mineralization behaviour and cell adhesion in vitro test results showed that partially crystalline had better mineralization behaviour, while the amorphous coating exhibited better cell adhesion and viability. In terms of type of texture, the most consistent results were found to the Thin texture in both in vitro tests, indicating that the spots promoted mineralization and cellular adhesion.